Influence of sound levels, secondary school student characteristics, sound types, and audiovisual interactions on the restorative potential of school environment soundscapes - Zheng, Leyi; Ren, Huanzhen; Shu, Shan; Gao, Haoyue; Fan, Junxi (Frontiers in Psychology, 2025)
Introduction Soundscapes can significantly impact individuals’ physical and mental health. However, the factors influencing the perceived restorativeness of soundscapes among secondary school students remain unclear. This study aims to explore the effects of school environment sound levels, individual characteristics, types of sounds, and audiovisual interactions on the perceived restorativeness soundscape (PRS) of secondary school students. Methods The study design includes measurements of sound pressure levels at 36 locations across six secondary schools in the Yangling District, a questionnaire survey involving 500 secondary school students, and analyses using difference, correlation, and structural equation models. Results The school environmental sound level of 59 dB(A) serves as a turning point for PRS. Significant personal factors affecting students’ PRS include gender, stress level, attention level, and noise disruption. Additionally, the frequency of natural and artificial sounds generated by student movements showed a positive correlation with PRS. The combination of audiovisual stimuli was found to enhance PRS among students. Furthermore, the primary factors influencing PRS are the appropriateness of the auditory environment and visual landscape evaluation, followed by the frequency of natural sounds. Conclusion Therefore, optimizing school soundscapes requires careful consideration of the appropriateness of the auditory environment, as well as the interest, harmony, and attractiveness of the visual surroundings. It is also crucial to enhance the frequency of natural sounds by incorporating greenery and other strategies. The findings of this study provide a theoretical basis for the optimization of secondary school soundscapes.